The Interaction of Influenza A NS1 and Cellular TRBP Protein Modulates the Function of RNA Interference Machinery - Wang, Qi; Wang, Jiaxin; Xu, Yan; Li, Zhe; Wang, Binbin; Li, Yang (Frontiers in Microbiology, 2022)
Influenza A virus (IAV), one of the most prevalent respiratory diseases, causes pandemics around the world. The multifunctional non-structural protein 1 (NS1) of IAV is a viral antagonist that suppresses host antiviral response. However, the mechanism by which NS1 modulates the RNA interference (RNAi) pathway remains unclear. Here, we identified interactions between NS1 proteins of Influenza A/PR8/34 (H1N1; IAV-PR8) and Influenza A/WSN/1/33 (H1N1; IAV-WSN) and Dicer’s cofactor TAR-RNA binding protein (TRBP). We found that the N-terminal RNA binding domain (RBD) of NS1 and the first two domains of TRBP protein mediated this interaction. Furthermore, two amino acid residues (Arg at position 38 and Lys at position 41) in NS1 were essential for the interaction. We generated TRBP knockout cells and found that NS1 instead of NS1 mutants (two-point mutations within NS1, R38A/K41A) inhibited the process of microRNA (miRNA) maturation by binding with TRBP. PR8-infected cells showed masking of short hairpin RNA (shRNA)-mediated RNAi, which was not observed after mutant virus-containing NS1 mutation (R38A/K41A, termed PR8/3841) infection. Moreover, abundant viral small interfering RNAs (vsiRNAs) were detected in vitro and in vivo upon PR8/3841 infection. We identify, for the first time, the interaction between NS1 and TRBP that affects host RNAi machinery.